The concepts evolution of capital and finance freedom movement in the Russian constitutional law - A. S. Seytumerov (Путеводитель предпринимателя, 2020)
In this article, the author investigated the concept of constitutional regulation of the free movement of capital and finance and reviewed the problem of its institutionalization in the Russian law.